Aerobic exercise prevents rarefaction of pial collaterals and increased stroke severity that occur with aging. Issue 11 (November 2017) - Rzechorzek, Wojciech; Zhang, Hua; Buckley, Brian K; Hua, Kunjie; Pomp, Daniel; Faber, James E
Variation in extent of the brain's collateral circulation is an important determinant of variation in the severity of stroke and efficacy of revascularization therapies. However, the number and diameter of pial collateral "arterioles" decrease with aging in associated with reduced eNOS and increased oxidative stress. We tested whether exercise reduces this aging-induced rarefaction. Twelve-month-old mice were randomized to sedentary or voluntary wheel-running. At 26 months' age, permanent MCA occlusion was followed 72 h later by determination of infarct volume and vascular casting after maximal dilation. The decline in collateral number and diameter and 2.4-fold increase in infarct volume evident in 26-versus 3-month-old sedentary mice were prevented by exercise-training. In contrast, number and diameter of the posterior communicating collateral "arteries" were unaffected by aging or exercise. Interestingly, diameter of the primary intracranial arteries increased with aging. Mechanistically, genetic overexpression of eNOS inhibited age-induced collateral rarefaction, and exercise increased eNOS and SOD2 and decreased the inflammatory marker NFkB assessed in hindlimb arteries. In conclusion, exercise prevented age-induced rarefaction of pial collaterals and reduced infarct volume. Aging also promoted outward remodeling of intracranial arteries. These effects were associated with increased eNOS and reduced markers of inflammation and aging in the vascular wall.